ANALISIS STRATEGI PROMOSI DAN SISTEM PELAYANAN TERHADAP KEPUASAN PELANGGAN FERRY BATAMFAST- BATAM - Diamon Sembiring; Muh Iqbal Yusuf Conoras (Ensiklopedia of Journal, 2023)
This study aimed to anlyse the influence of the partial strategy promotion on costumer’s satisfaction customer, to analysis the influence of the partial service system on customer’s satisfaction customer and to analysis strategy promotion and service system on satisfaction customer simultaneously. Base on the results of the analysis indicate that the promotion is significantly influence the satisfaction customer of the customer of the PT. Batamfast Indonesia , indicated by the t significant value of 0.000 smaller than α = 0,05 (0,000 < 0,05) with regression coefficient of 1.069. System service a significant effect on the satisfaction customer of PT. Batamfast Indonesia, indicated by the t significant value of 0.365 less than α = 0,05 (0,005 < 0,05) with regression co-efficient of 0.076. Promotion and the system service is simultaneously significant effecting the satisfaction customer of customer PT. Batamfast Indonesia, indicated by F significant value of 0.000 smaller than α = 0,05 (0,000 < 0,05) and were able to contribute to satisfaction customer variables of 0.804 or 80,4%. The remaining 19,6% is influenced by other variables that are not examined in this study.